Soroprevalência e características epidemiológicas da toxoplasmose em área rural de Santa Teresa, Espírito Santo - Buery, Julyana Cerqueira (2013)
This study aims to analyze the prevalence and annual incidence of asymptomatic infection caused by the protozoan Toxoplasma gondii. Three hundred and eleven samples were evaluated from 79 individuals living in rural areas of Santa Teresa city, in the state of Espírito Santo. Demographic and socioeconomic data and factors associated with infection were collected using questionnaires, which were updated quarterly. The selection of subjects was made from a pre-existing cohort, based in a study of asymptomatic malaria cases in the mountainous region of the state. After selection of the participants, plasma was collected quarterly for performing the serologic tests anti-T. gondii using ELISA techniques and, in addition, IgG avidity was tested for positive samples to evaluate the rate of seroconversion in this cohort. The prevalence of T. gondii infection in this community was 67.1% and the incidence was 6,2 per 100 person-year of observation. There was no statistically significant association between individuals who had contact with cats or between the consumption of pork or lamb meat, even raw or undercooked, and toxoplasmosis. According to multivariate analysis, the only risk factor related with infection seems to be an increasing age (OR = 1.086). Confirming published data, the statistical analysis showed that, for each year that passes, the individuals are 8.6% most likely to acquire toxoplasmosis. This study confirms that the inhabitants of rural communities in the mountainous region of the Holy Spirit are highly exposed to Toxoplasma gondii and have little knowledge about the disease, which makes them vulnerable to exposure